2018
DOI: 10.1111/birt.12346
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for obstetric anal sphincter injuries: A retrospective nationwide study

Abstract: BackgroundIn view of the reported increase in obstetric anal sphincter injuries, the objective of this study was to evaluate the incidence of such injuries over time and the associated risk and protective factors.MethodsThis was a retrospective cohort study from a national database of 168 137 primiparous women with term, singleton, cephalic, vaginal delivery between 2008 and 2014. The main outcome measure was obstetric anal sphincter injury. A multivariate regression model was used to identify risk and protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
3
20
0
2
Order By: Relevance
“…Similar to previous studies [41, 46, 47], an increase in OASIS was observed. This rise could be associated with the decrease in episiotomy rates [41], but may also be influenced by the increases in instrumental delivery and nulliparity which are known risk factors for OASIS [8].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous studies [41, 46, 47], an increase in OASIS was observed. This rise could be associated with the decrease in episiotomy rates [41], but may also be influenced by the increases in instrumental delivery and nulliparity which are known risk factors for OASIS [8].…”
Section: Discussionsupporting
confidence: 90%
“…Perineal edema is associated with perineal pain and postpartum discomfort after vaginal delivery. Rapid recovery from perineal edema allows for the resumption of maternal activities of daily living, such as lying down, sitting, walking, infant care, breastfeeding, and urination 429. Our study showed that a high percentage of women in the HAase injection group had improved perineal edema at 24 hours, which suggests that HAase injections improve tissue diffusion and the resorption rate of excess fluid.…”
Section: Discussionmentioning
confidence: 52%
“…The reported incidence of perineal trauma during vaginal delivery is approximately 85%, but can vary in different settings, depending on clinical practice and conditions during vaginal delivery 2. Anal sphincter injuries, which are the most severe perineal trauma events, have gradually increased in number over the last several decades, with incidence rates ranging from 4.1% to 16.0% in several population-based studies 34. Perineal trauma during vaginal delivery has been shown to be associated with significant maternal morbidities, including blood loss, perineal pain, infection, dyspareunia, urinary incontinence, flatus, and fecal incontinence, and to lead to the development of comorbidities, including sexual dysfunction, pelvic organ prolapse, and rectovaginal and vesicovaginal fistulas 356.…”
Section: Introductionmentioning
confidence: 99%
“…1 In our analysis, the main supine position was the semi-recumbent position, with 53.1% of all births, and not the lithotomy position. On the other hand, Marschalek et al, 2 analyzing a national database, reported that the birth position had no effect on OASIs. Our interpretation has raised questions that range from a long history of births in the horizontal position to the effective approaches for perineal protection in upright positions.…”
Section: Discussionmentioning
confidence: 98%
“…The best maternal position adopted during the pelvic phase to avoid perineal damage is an issue that is still controversial, depending on a set of multifactorial predictors and specific subgroups of analysis. [1][2][3] High rates of obstetric anal sphincter injuries (OASIs) among women giving birth in the lithotomy position were reported in a population-based study 1 in Sweden on term non-instrumental births without episiotomy. However, another population-based research 2 in Austria, including primiparous term births, did not prove any effect of the birth positions on OASIs.…”
Section: Introductionmentioning
confidence: 99%